The Influence of E-Wallet Usage on the Decision to Use the Dana Application for Transactions among State University Students in Central Java - Annisa Noviana Ramadhani; Moechammad Nasir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Modern technology has provided significant convenience in everyday life, including in economic transactions. One of the most visible innovations is the use of electronic wallets (e-wallets), which enable practical and efficient digital transactions. This study's goal is to comprehend the impact of usability, service features, and lifestyle on students' decisions when conducting transactions with the DANA application. This research utilizes a survey method combined with a quantitative method. Data were collected through questionnaires from 280 respondents consisting of students from Diponegoro University (UNDIP) and Sebelas Maret University (UNS) in Central Java. The Partial Least Square (PLS) method was used to analyze the data. According to the study's findings, usability service features, and lifestyle significantly influence the decision to use the application. Ease of use increases technology adoption, while innovative features and students' digital lifestyles drive interest and decisions to use the DANA application. The findings of this research contribute to the DANA application development strategy to continue to improve convenience, service features, and relevance to users' lifestyles, so that they can remain competitive in the digital market. However, this study has limitations covering a limited area, and exploring other variables in future research is recommended.